2005
DOI: 10.1002/mrm.20700
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial first pass perfusion: Steady‐state free precession versus spoiled gradient echo and segmented echo planar imaging

Abstract: The imaging sequences used in first pass (FP) perfusion to date have important limitations in contrast-to-noise ratio (CNR), temporal and spatial resolution, and myocardial coverage. As a result, controversy exists about optimal imaging strategies for FP myocardial perfusion. Since imaging performance varies from subject to subject, it is difficult to form conclusions without direct comparison of different sequences in the same subject. The purpose of this study was to directly compare the saturation recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 18 publications
3
51
0
Order By: Relevance
“…The SSFP sequence has a superior signal to noise ratio when compared with gradient echo sequences (21). Hence, we were able to use a small amount of contrast (average 1-2 mL) at a concentration much below the threshold for contrast saturation effects to analyze lung perfusion quantitatively (21,22). Our absolute perfusion results in normal volunteers were comparable to published data using a 3D gradient echo sequence (15).…”
Section: Discussionsupporting
confidence: 89%
“…The SSFP sequence has a superior signal to noise ratio when compared with gradient echo sequences (21). Hence, we were able to use a small amount of contrast (average 1-2 mL) at a concentration much below the threshold for contrast saturation effects to analyze lung perfusion quantitatively (21,22). Our absolute perfusion results in normal volunteers were comparable to published data using a 3D gradient echo sequence (15).…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, perfusion MRI yields sensitivities and specificities of 89% and 79% (AUC 0.92) by an observer with CMR training level of 3, and 83% and 71% (AUC 0.84) by an observer with CMR training level of 2 for the detection of patients with obstructive CAD. We employed saturation-recovery SSFP sequence for MR perfusion imaging in this study since this technique has been shown to have better signal-to-noise and contrast-to-noise ratio compared with spoiled gradient-echo and segmented echo-planar techniques [25]. Although SSFP perfusion is considered more susceptible to dark-rim artifacts, use of SSFP sequence resulted in at least no appreciable deterioration in diagnostic performance in our study cohort in comparison with previous reports.…”
Section: Discussionmentioning
confidence: 75%
“…Previous work has shown that car- diac motion during image acquisition (31) and spatial resolution (32) may have a significant effect on the appearance of artifacts. Previous authors suggest that the prevalence of banding artifacts with SSFP is related to its greater inherent CNR in comparison to the other sequences (33). In this study SSFP had the greatest CNR, but also the most artifacts.…”
Section: Discussionmentioning
confidence: 42%
“…Comparison of hEPI and GRE, showed comparable artifact and ischemia scores for hEPI (29). However, many studies have not necessarily had a suitable clinical dimension being limited by using doped phantoms, not comparing sequences in the same patients, performing only rest perfusion studies, or not systematically assessing the presence and severity of artifacts (33,34). In our study, hEPI scoring the least artifacts and the highest diagnostic confidence is consistent with the findings of Muhling et al (35), who demonstrated that interobserver agreement as well as sensitivity to perfusion defects is related to both image quality and SNR.…”
Section: Discussionmentioning
confidence: 99%